Volume 2 2004
DOI: 10.1115/esda2004-58521
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of the Human Head and Neck for Frontal and Lateral Impacts

Abstract: This paper presents the development and validation of a three-dimensional computational model of the human head and neck. The model has been produced to study the mechanics of the human cervical spine in response to automobile impacts. The complete head-neck model has been used to simulate 15g frontal and 7g lateral impacts with the resulting motion compared against response corridors derived from sled acceleration tests using human volunteers. The effect of passive and fully active muscle behaviour has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Good agreement was seen for both impact directions. For more information regarding the model development and validation the reader is referred to [22].…”
Section: Model Validationmentioning
confidence: 99%
“…Good agreement was seen for both impact directions. For more information regarding the model development and validation the reader is referred to [22].…”
Section: Model Validationmentioning
confidence: 99%
“…The effect of passive and fully active muscle behaviour was investigated and was shown that for both impact directions the inclusion of active muscle tensioning results in closest agreement with the experimental data. Good agreement was seen for both impact directions [26]. The model has also been implemented without musculature to simulate bench-top trauma experiments using cadaveric isolated cervical spine specimens.…”
Section: Multi-body Model Development and Validationmentioning
confidence: 95%
“…The model reproduces the head and neck of an adult in an upright sitting position with the arrangement of the cervical vertebrae representing the natural lordosis of the neck with mid-sagittal symmetry assumed [16]. The three-dimensional geometry of the vertebrae and skull were defined using Solid-Edge, version 9, CAD software from EDS (Electronic Data Systems Corporation).…”
Section: Multi-body Model Development and Validationmentioning
confidence: 99%
“…PMHS cervical spine experiments conducted by the same authors [1,3] Limitations due to PMHS cervical spine study, no intervertebral translation measured Validation corridors for the experimental data were derived from the same author group; previously these corridors were not published. [81] Tissue-level based model. Multi-Body Dynamics head-and-neck model designed by Van-Lopik.…”
Section: Computational Models With Intervertebral Motion Validationmentioning
confidence: 99%
“…The experimental data was once again from the Yale University School of Medicine study [28,39,40]. This allows a direct comparison of the Hoover & Meguid to the Van Lopik [81] model: Van Lopiks model, which is far more detailed, produced better results for the peak flexion in the upper cervical joints in the early trauma phase, but performed worse in the peak extension of the joint C1-C2 in the later trauma phase. However, the Yale University School of Medicine study hypothesize that the lower cervical spine is at higher risk.…”
Section: Pmhs Cervical Spine Experiments Conducted By the Yale Univermentioning
confidence: 99%